COMPARATIVE CHARACTERISTICS OF CLINICAL MANIFESTATIONS OF MENOPAUSE IN WOMEN WITH PHYSIOLOGICAL MENOPAUSE AND AFTER TOTAL OVARIECTOMY WHILE USING NON-HORMONAL DRUGS - Геник, Н. І.; Гінчицька, Л. В.; Стоцький, С. С.; Оріщак, І. К. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The problem of menopause attracts attention for many decades not only gynecologists but urologists, cardiologists, psychiatrists and other doctors. Receptors for estrogen and progesterone are found not only in the tissues of target organs (uterus, ovaries, breast), but also in other tissues: in the urethra, bladder, pelvic floor muscles, brain cells, myocardium, walls of the arteries, bone tissue, skin, oral mucosa, larynx, conjunctiva and others. To test the effectiveness of menopausal disorders treatment was examined two groups of women: I group – 20 women with physiological menopause, the second group – 20 women after total ovariectomy. As nonhormonal drug we used Menopace (multivitamin with minerals) for the treatment of menopausal manifestations, the effect of which is caused by substances that it contains. Symptoms of climax at physiological and surgical menopause for three months was studied using the modified menopausal index (MMI) by E.V. Uvarov. Dynamic of clinical progress shows that in women from basic group with physiological menopause under conditions of using Menopace decreased symptoms of neurovegetative syndrome.Within three months of treatment, there are patients with absence of clinical manifestations (20,0%) and decreasing number of women with medium (from 70,0% to 10,0%) and the absence of a high severity of the syndrome by increasing patients with mild degree (from 20,0% to 70,0%). Thus, the percentage of medium and high severity decreased by 60.0% and 10.0% respectively. While in women from comparative group occurs decreasing of patients without clinical manifestations on 20%, by increasing the number of women with milddegree (from 50,0% to 60,0%) and medium (from 20,0% to 30,0% ) degree of severity of symptoms and high degree of severity. The data suggest that for reliefof climax symptoms is effective to use non-hormonal drug Menopace in combination with a healthy lifestyle and proper nutrition.